Indonesia’s Smart City: Does Legal Framework Matter? - Atmaheni, Amanda Amilia; Adianto, Joko (International Journal of Built Environment and Scientific Research, 2024)
This article delves into the pressing challenges encountered in the advancement of smart city initiatives in Indonesia, particularly emphasizing the critical necessity for comprehensive standard guidelines. Despite nationwide excitement surrounding smart city development, a lack of a unified regulatory framework has led to inconsistent urban planning strategies, devoid of a unified direction. The article's main goal is to emphasize the importance of establishing laws governing smart city development in Indonesia. Additionally, it aims to showcase innovative efforts undertaken by various groups to address this regulatory gap and promote inclusive smart city development. This study examines the challenges hindering Smart City development in Indonesia. By examining relevant academic literature and legal documents, the study analyzes the challenges stemming from the fragmented legal landscape. The analysis highlights how this lack of national coherence hinders national coherence, disrupts project implementation, and impedes program evaluation.. Overall, the article advocates for prioritizing a national legal framework that will foster a more stable environment, benefiting researchers, policymakers, and ultimately, the citizens who stand to gain from successful Smart City initiatives.